Mitochondrial DNA sequencing reveals association of variants and haplogroup M33a2′3 with High altitude pulmonary edema susceptibility in Indian male lowlanders - Sharma, Swati; Singh, Sayar; Gupta, Rajinder K.; Ganju, Lilly; Singh, Shashi Bala; Kumar, Bhuvnesh; Singh, Yamini (Scientific reports, 2019)
High Altitude Pulmonary Edema (HAPE) is a threatening disorder caused due to acute exposure to high altitude above 3000 m. Apart from multiple factors involved, the genetic factors also play an important function in the pathogenesis of HAPE. This study aims to evaluate the role of mtDNA polymorphism and their association with haplogroup in understanding the etiology of HAPE. In this study, all the HAPE susceptible and acclimatized control subjects could be classified into nine haplogroups pertaining mostly to Macrohaplogroup M and U. The frequency of haplogroup M was significantly higher in HAPE susceptibles whereas the haplogroup M33a2′3 was found only in HAPE susceptibles. The variant G4491A and A4944G of MT-ND2, A14002G of MT-ND5, and C8562T of MT-ATP8, were definition site of haplogroup M33a2′3. The frequency of A10398G of MT-ND3, A8701G of MT-ATP6 and C14766T of MT-CYB genes were significantly higher in HAPE susceptibles. mtDNA copy number also plays a significant synergistic role in HAPE susceptibility. Our findings suggests that variants in MT-ND2 and MT-ND5 were predicted to confer decreased protein stability in HAPE susceptibles and in particular, highly conserved variants G4491A, A4944G and A14002G associated with haplogroup M33a2′3 may be the primary cause of susceptibility to HAPE in Indian male lowlanders.